Molecular dynamic simulations of the core–shell microsphere of nanosilica grafted by acrylamide acrylic acid copolymer PAMAA: study of its microstructure and interaction between microsphere and additives. (13th April 2016) - Dai, Shanshan; Zhang, Jinghan; Zhang, Tailiang; Huang, Zhiyu; Quan, Hongping; Lu, Hongsheng; Zhao, Xiaowen
Abstract : Different additives have a remarkable effect on the microstructure of microsphere in aqueous solution. Abstract : Nanosilica grafted by acrylamide (AM) acrylic acid (AA) copolymer (PAMAA) is designed in this study to make a functional material, where nano-SiO2 provides the rigidity and strength and the copolymer the elasticity and flexibility. The resulting microsphere with a core–shell structure is able to enter, expand, shut off and be removed from deep layers of oilfields. Qualitative results can be easily obtained from normal experimental methods, but many quantitative relationships are still missing. To solve the problem mentioned above, molecular dynamic (MD) simulation is applied in this work to study the microstructure of microspheres and the interaction between microsphere and additives. Aqueous solutions (S1), as well as solutions with sodium dodecyl sulfate (SDS, S2), dodecyl trimethyl ammonium bromide (DTAB, S3), and alcohol ethoxylate (AEO, n = 3, S4) are built. The non-bond energy, radius of gyration (ROG) of microsphere, radial distribution function (RDF) for microsphere–additive pairs and mean square displacement (MSD) of polymer chains in these 4 different solutions are calculated at 325 K, 350 K and 375 K. The results show that addition of surfactants leads to a more stretched out polymer chain structure. The hydration effect and mobility of the polymer chain increase in both aqueous and surfactant solutions as temperature increases.